2018
DOI: 10.1556/2006.7.2018.111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy of a specialized psychotherapy program for Internet Gaming Disorder

Abstract: Background and aimsInternet Gaming Disorder (IGD) has become health concern around the world, and specialized health services for the treatment of IGD are emerging. Despite the increase in such services, few studies have examined the efficacy of psychological treatments for IGD. The primary aim of this study was to assess the efficacy of a specialized psychotherapy program for adolescents with IGD [i.e., the “Programa Individualizado Psicoterapéutico para la Adicción a las Tecnologías de la Información y la Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 59 publications
2
58
0
8
Order By: Relevance
“…The CBT programme in the current study was responsible for improvement in 17% more patients with IGD than was supportive therapy. There have been several studies of CBT for IGD that supported our results (Torres‐Rodríguez, Griffiths, Carbonell, & Oberst, ; Wölfling et al, ). Torres‐Rodriguez et al (2018) suggested that CBT for IGD was effective for improvement of IGD.…”
Section: Discussionsupporting
confidence: 87%
“…The CBT programme in the current study was responsible for improvement in 17% more patients with IGD than was supportive therapy. There have been several studies of CBT for IGD that supported our results (Torres‐Rodríguez, Griffiths, Carbonell, & Oberst, ; Wölfling et al, ). Torres‐Rodriguez et al (2018) suggested that CBT for IGD was effective for improvement of IGD.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of comorbidity, IGD has been associated with a wide spectrum of psychological problems including depression, anxiety, social phobias, poorer school performance, and sleep disorders [36,[39][40][41][42]. In addition, studies have begun to appear comprising clinical samples demanding psychological treatment, which meet the criteria for the disorder [38,43]. In the study by Martín-Fernández et al [38], all participants had diagnostic comorbidity, in accordance with other studies [44,45].…”
Section: Introductionsupporting
confidence: 69%
“…Low efficiency in information processing may limit individuals’ ability to access effective emotion regulation strategies. Cognitive-behavioral therapy for IA aims to increase the clients’ ability of impulse control by training clients’ skills to monitor their inner feelings and control impulse behaviors [ 41 , 42 , 43 ]. Research also found that electro-acupuncture had an advantage over psychological intervention in terms of impulsivity control in adolescents with IA [ 44 ].…”
Section: Discussionmentioning
confidence: 99%